1989
DOI: 10.1002/bit.260340304
|View full text |Cite
|
Sign up to set email alerts
|

Improved method for preparing high maltose conversion syrups

Abstract: An improved method is presented for producing high maltose conversion syrups from liquefied and raw starch. It comprises saccharifying the starch at higher temperatures than presently used with environmentally compatible thermostable beta-amylase and other thermostable enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Outros tipos de enzimas amilolíticas, como a ciclomaltodextrina gluconosiltranferase (CGTase), que convertem oligodextrinas em ciclodextrinas, a α-glucosidase, que libera glicose a partir de dextrinas curtas e a pululanase, que atua sobre o pululano, também apresentam formas termoestáveies 109,110 . Espécies do gênero Themococcus produzem CGTases com atuação a 90 e 100 °C e estabilidade a 105 °C…”
Section: Amilases Termoestáveisunclassified
“…Outros tipos de enzimas amilolíticas, como a ciclomaltodextrina gluconosiltranferase (CGTase), que convertem oligodextrinas em ciclodextrinas, a α-glucosidase, que libera glicose a partir de dextrinas curtas e a pululanase, que atua sobre o pululano, também apresentam formas termoestáveies 109,110 . Espécies do gênero Themococcus produzem CGTases com atuação a 90 e 100 °C e estabilidade a 105 °C…”
Section: Amilases Termoestáveisunclassified
“…β-Amylase alone does not lead to high maltose concentration because it is not able to bypass 1,6-α-linkages. Adding debranching enzyme such as pullulanase is the only way of obtaining extremely high maltose syrups [17,38,44]. A study on the relationship between final maltose and enzyme concentrations showed that conversion increased with increasing pullulanase to β-amylase ratio up to a limit when there were no longer 1,6-α-linkages to be broken [45].…”
Section: Hydrolysis With Liquefactionmentioning
confidence: 99%
“…The use of enzymes working at low temperatures entails high viscosity as well as retrogradation products and may introduce strong limitations in saccharification. Choosing thermostable enzymes able to support elevated temperature such as β-amylase and pullulanase frees from such difficulties [44].…”
Section: Hydrolysis With Liquefactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Undesirable products like branched oligosaccharides, panose, isopanose and isomaltose are formed. Improvement of the starch-conversion process by finding new efficient and suitable enzymes with high thermostabilities, functioning in the acidic to neutral pH range, and independent of cations such as Ca 2+ for stability/activity would significantly lower the cost of sugar syrup production [2][3][4]. Increasing the starch-saccharification process temperature would result in several benefits such as higher substrate concentrations, decreased viscosity and lower pumping costs, limited risk of bacterial contamination, increased reaction rates and decrease of operation time, lower costs of enzyme purification, and longer catalyst half-life, due to increased enzyme thermostability [4].…”
Section: Introductionmentioning
confidence: 99%